Giant pandas (Carnivora: Ailuropoda melanoleuca) and living hominoids converge on lumbar vertebral adaptations to orthograde trunk posture. Issue 88 (November 2015) - Russo, Gabrielle A.; Williams, Scott A.
Abstract: Living hominoids share a common body plan characterized by a gradient of derived postcranial features that distinguish them from their closest living relatives, cercopithecoid monkeys. However, the evolutionary scenario(s) that led to the derived postcranial features of hominoids are uncertain. Explanations are complicated by the fact that living hominoids vary considerably in positional behaviors, and some Miocene hominoids are morphologically, and therefore probably behaviorally, distinct from modern hominoids. Comparative studies that aim to identify morphologies associated with specific components of positional behavioral repertoires are an important avenue of research that can improve our understanding of the evolution and adaptive significance of the hominoid postcranium. Here, we employ a comparative approach to offer additional insight into the evolution of the hominoid lumbar vertebral column. Specifically, we tested whether giant pandas (Carnivora: Ailuropoda melanoleuca ) converge with living hominoids on lumbar vertebral adaptations to the single component of their respective positional behavioral repertoires that they share—orthograde (i.e., upright) trunk posture. We compare lumbar vertebral morphologies of Ailuropoda to those of other living ursids and caniform outgroups (northern raccoons and gray wolves). Mirroring known differences between living hominoids and cercopithecoids, Ailuropoda generally exhibits fewer, craniocaudally shorter lumbar vertebrae with more dorsally positioned transverse processes that are more dorsally oriented and laterally directed, and taller, more caudally directed spinous processes than other caniforms in the sample. Our comparative evidence lends support to a potential evolutionary scenario in which the acquisition of hominoid-like lumbar vertebral morphologies may have evolved for generalized orthograde behaviors and could have been exapted for suspensory behavior in crown hominoids and for other locomotor specializations (e.g., brachiation) in extant lineages.